2020
DOI: 10.3390/ijerph17249188
|View full text |Cite
|
Sign up to set email alerts
|

Are You Tired of Working amid the Pandemic? The Role of Professional Identity and Job Satisfaction against Job Burnout

Abstract: With the outbreak of novel coronavirus in 2019, most universities changed from traditional offline teaching to online teaching, which brought about a large amount of problems, including teachers’ physical and mental problems. Because of teaching on the computer screen for a long period of time, the teacher lacks communication and can act casually. With long-term accumulation, the problem of teachers’ job burnout has become increasingly serious. The main purpose of this study was to examine the influence of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
91
2
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(106 citation statements)
references
References 69 publications
5
91
2
8
Order By: Relevance
“…Previous research has found that professionals who provide social and humanistic services (including teachers from different teaching fields) often experience job burnout [24][25][26]. In the educational context, many factors can induce job burnout syndrome, mainly individual physiological and psychological factors, communicative relations, and environmental factors [27]. Relevant research has shown that teachers' job burnout is caused by their long-term and extensive job stress, and its main symptoms are tension and fatigue in job perception, excessive obedience in the face of school and family, and low personal accomplishment [28].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has found that professionals who provide social and humanistic services (including teachers from different teaching fields) often experience job burnout [24][25][26]. In the educational context, many factors can induce job burnout syndrome, mainly individual physiological and psychological factors, communicative relations, and environmental factors [27]. Relevant research has shown that teachers' job burnout is caused by their long-term and extensive job stress, and its main symptoms are tension and fatigue in job perception, excessive obedience in the face of school and family, and low personal accomplishment [28].…”
Section: Introductionmentioning
confidence: 99%
“…It has three characteristics: (1) the feeling of energy expenditure or exhaustion; (2) increasing the perceptual distance from work, or work-related negative emotions or feelings of cynicism; (3) reducing professional performance [ 7 ]. In addition to the negative impact on individual physical and mental health, burnout also affects organizational commitment, turnover intention, and job performance [ 8 ]. The work characteristics of extreme intensity, high stress, and long working hours of health professionals make them one of the most susceptible groups to generate job burnout [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prior literature has focused mainly on burnout definition, adjustments, prevention, and factors associated with burnout syndrome related to teachers (such as self-efficacy, self-esteem), students (such as relatedness), organization, and environmental (for example, attitudes towards inclusion and organization support) and socio-demographic factors (such as gender, age, and work experience) [ 4 , 8 , 9 , 10 , 11 , 12 , 13 ]. More recently scholars have paid special attention to teacher burnout during the COVID-19 pandemic, mainly examining the switch from face-to-face classes to the online setting [ 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the sense of belonging to the academic community and professional identity have attracted the attention of researchers [ 14 , 26 ]. This study also examined the sense of belonging in e-learning and b-learning modalities before and after COVID-19 disruption.…”
Section: Introductionmentioning
confidence: 99%